Peningkatan Literasi Siswa Sekolah Dasar Melalui Pengembangan Media Interaktif Berbasis Web - Lesi Anggraini; Yadi (BETRIK, 2025)
Literacy is a key aspect in the learning process because all students need to have good literacy skills to be able to process information optimally. Literacy is not only limited to reading ability, but also includes the ability to analyze, understand, and translate information based on written text. Improving student literacy in schools is crucial to support the achievement of literacy competencies as a whole. However, the limited learning media that can attract students' interest in literacy remains an obstacle, as seen from the learning process that is still predominantly using the lecture method. This study aims to determine the improvement of student literacy through the use of web-based interactive media. Media development was carried out using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the study showed an increase in student literacy scores based on a comparison of pretest and posttest scores given to 35 respondents, with an increase of 35%. In addition, the practicality test showed a score of 93.47% with a practical category. Thus, web-based interactive media can be an effective approach in improving student literacy because it can stimulate optimal cognitive development.